Analysis of the technical efficiency of yam cultivation (Dioscorea spp.) in the Caribbean Region of Colombia - Martinez Reina, Antonio Maria; Tordecilla Zumaque, Lilibeth; Grandett Martinez, Liliana Maria; Regino Hernandez, Sol Mara; Luna Castellanos, Lily Lorena; Pérez Cantero, Shirley Patricia (Universidad Pedagógica y Tecnológica de Colombia UPTC, 2024)
The objective was to analyze the technical efficiency of yam cultivation in producing areas of the Caribbean Region. The data were obtained through 98 structured surveys applied to experienced farmers, which included socioeconomic information such as: age, schooling, size of the cultivated area, physical crop yields, and production destination. The sampling technique was simple and applied at random. The data were analyzed in the SPSS program, and techniques such as descriptive statistics and measures of central tendency were used. Likewise, a Cobb-Douglas type econometric model was designed that allowed formulation of a production function and estimation of the parameter values. The results showed that the production efficiency was low because of underutilization of some factors, such as labor, which is 78 wages on average, excessive for the cultivation of one hectare of yams; in addition, fertilizers are used without a soil analysis and without considering the nutritional requirements of the crop. The seed is an important factor that contributes to increases in production with a coefficient of 0.033881, so, if its quality is improved, efficiency can be increased. Experience and schooling contributed the most to the efficiency of the yam cultivation. Farmers can increase productivity with a better use of resources.